Phase Transformations in Steels : Diffusionless Transformations, High Strength Steels, Modelling And Advanced Analytical Techniques. - Pereloma, E. (Woodhead Publishing series in metals and surface engineering., 2012)
The processing-microstructure-property relationships in steels continue to present challenges to researchers because of the complexity of phase transformation reactions and the wide spectrum of microstructures and properties achievable. This major two-volume work summarises the current state of research on phase transformations in steels and its implications for the emergence of new steels with enhanced engineering properties. Volume 2 reviews current research on diffusionless transformations and phase transformations in high strength steels, as well as advances in modelling and analyti.